THE VISITOR EXPERIENCE IN MUSLIM FAIR: THE CASE FROM MUSLIM FASHION FESTIVAL (MUFFEST+) 2022 IN INDONESIA - Nurmala Rossi, Fetty; Erfinda, Yosi; Putri, Ratu (International Journal of Sustainable Competitiveness on Tourism, 2024)
Jakarta is one of the priority destinations as a business event developed by the government, especially in the exhibition sector, which has increased both in terms of the number and quality of exhibitions, being one of the fastest-growing sectors in the tourism industry. For a good-quality event, it is necessary to create an experience from the visitor's side. This study analysed the visitor experience at the Muslim Fashion Festival in 2022. The qualitative descriptive method was used as a research method with a theoretical-descriptive analysis approach that emphasises the analysis of numerical data, which was then processed with statistical methods through a questionnaire survey given to visitors and distributed during the event. The findings highlighted visitor priority in selecting programmes and services as an essential point in the event experience. This proves that event programmes and services significantly impact visitors to get an interesting experience and can influence purchase decisions on these products for visitors. However, the overall statement in the aspect of self-experience is that visitors are allowed to engage and interact with the events, which also provides a memorable experience.